Improving Computational Thinking Skills Through The Implementation of Project-Based Learning According to Student Differentiation in Physics Learning - Rita Iva Fatmala; Putut Marwoto; Ellianawati Ellianawati (Physics Communication, 2025)
The research aims to determine the effectiveness of project-based learning by paying attention to student differentiation to improve computational thinking skills. The research is based on students' computational thinking skills, which are still below standard, namely below of 50% at each stage, including decomposition, pattern recognition, abstraction, and algorithms. This research is classroom action research carried out over three learning cycles. The results of the research show that there is an increase in students' computational thinking skills in each learning cycle given. In the first and second cycles, the level of achievement of students' computational thinking skills reached 22.8% and 54.29%, meaning that what was originally in the very low category became low. After that, in the third cycle the level of achievement of students' computational thinking skills in the high category reached 88.57%. The gain test results in the first and second cycles were in the medium category with n- gain scores of 0.40 and 0.52. Furthermore, in the third cycle, an n-gain of 0.71 or high category level. These results indicates that the implementation of project-based learning according to student differentiation in physics learning was effective in improving computational thinking skills.